2018
DOI: 10.1111/epi.14574
|View full text |Cite
|
Sign up to set email alerts
|

A novel GABAergic dysfunction in human Dravet syndrome

Abstract: Summary Objective Dravet syndrome is a rare neurodevelopmental disease, characterized by general cognitive impairment and severe refractory seizures. The majority of patients carry the gene mutation SCN1A, leading to a defective sodium channel that contributes to pathogenic brain excitability. A γ‐aminobutyric acid (GABAergic) impairment, as in other neurodevelopmental diseases, has been proposed as an additional mechanism, suggesting that seizures could be alleviated by GABAergic therapies. However, up to now… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 51 publications
7
47
0
Order By: Relevance
“…In agreement with our previous studies (Roseti et al, 2013;Ruffolo et al, 2018), this variability in I GABA amplitude was not dependent by which patient was used for membranes preparation, since each human sample was obtained from the same amount of tissue, but it was probably due to a different expression efficiency in the different oocytes.…”
Section: Resultssupporting
confidence: 91%
“…In agreement with our previous studies (Roseti et al, 2013;Ruffolo et al, 2018), this variability in I GABA amplitude was not dependent by which patient was used for membranes preparation, since each human sample was obtained from the same amount of tissue, but it was probably due to a different expression efficiency in the different oocytes.…”
Section: Resultssupporting
confidence: 91%
“…Other studies also investigated the involvement of CBD on GABA A Rs mediated transmission: by using human tissues obtained from patients suffering of Dravet syndrome (DS) and tuberous sclerosis complex (TSC) it was demonstrated that CBD at 5 µM concentration is able to significantly increase GABA-evoked currents amplitude, acting as a positive allosteric modulator. This effect was totally reverted after a short wash-out [62] and was comparable to that of a typical benzodiazepine (BDZ), i.e., flunitrazepam. Indeed, CBD was able to significantly increase evoked GABA A Rs currents, both on α1and α2-containing receptors, with an efficacy that was very similar to the flunitrazepam.…”
Section: Cannabinoids and Gaba A Rsmentioning
confidence: 70%
“…In fact, the increase in TRPV1 might be one of the mechanisms promoting excitatory/inhibitory imbalance in epilepsy 17,18 and specifically in drug‐resistant epilepsy related to SYNGAP1 mutations. CBD is known to generate a rapid activation and desensitization of TRPV1 in a dose‐dependent manner 19–22 and might target in this way the TRPV1 increase induced by SYNGAP1 mutations resulting in seizures’ reduction.…”
Section: Discussionmentioning
confidence: 99%